2016
DOI: 10.6018/analesps.32.3.259401
|View full text |Cite
|
Sign up to set email alerts
|

La Identificación del talento verbal y matemático: la relevancia de las medidas fuera de nivel

Abstract: Título: Identificación del Talento Verbal y Matemático: La relevancia de la medida "out of level". Resumen: El presente estudio tiene dos objetivos principales. Por una parte, se ofrece una revisión conceptual de la literatura junto con los trabajos realizados en España por los autores acerca del modelo de identificación del talento, conocido en la literatura internacional como Talent Search model o Talent Search concept. Este modelo creado por J.C. Stanley en los EE.UU. a principios de los 70 ha dado lugar a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…As in many other countries, the population of gifted students in Spain presents some peculiarities that should be highlighted. Among them, their geographic and school dispersion, the diversity of identification criteria, the lack of systematic detection processes leading to infra-identification, among others [48]. According to the Ministry of Education of Spain, there were 27,133 gifted students in 2017 (last available year).…”
Section: Methodsmentioning
confidence: 99%
“…As in many other countries, the population of gifted students in Spain presents some peculiarities that should be highlighted. Among them, their geographic and school dispersion, the diversity of identification criteria, the lack of systematic detection processes leading to infra-identification, among others [48]. According to the Ministry of Education of Spain, there were 27,133 gifted students in 2017 (last available year).…”
Section: Methodsmentioning
confidence: 99%
“…Many scholars have suggested that the high ceilings that exist in above-level tests may mean that they are more discriminatory in the assessment of gifted students in comparison to many other instruments (Rambo-Hernandez & Warne, 2015; Warne, 2012, 2014; Warne et al, 2016). Above-level testing is a particularly popular practice in Talent Search programs, such as the Belin-Blank Exceptional Students Talent Search conducted at the University of Iowa (Assouline & Lupkowski-Shoplik, 2012; Jung, Barnett, Gross, & McCormick, 2011; Rambo-Hernandez & Warne, 2015; Swiatek, 2007; Tourón & Tourón, 2011, 2016)…”
Section: Common Types Of Assessmentsmentioning
confidence: 99%
“…Thus, to the extent that there is an inadequate adaptation of the teaching-learning process to the characteristics of students with high abilities, this school context, as found in other studies [ 16 , 55 , 56 ] state, puts these students at a disadvantage, and they tend to become bored, which leads to a general lack of motivation and, therefore, to failure at school.…”
Section: Discussionmentioning
confidence: 92%
“…Concerning this, it is important to focus on the diversity of areas (cognitive, social and emotional) in order to make an adequate diagnosis and establish measures for action [ 2 , 5 ]. In addition, according to Tourón et al [ 16 ], the crucial point in the case of this type of student is not to determine a precise diagnosis of giftedness and all its components—only from an interdisciplinary approach is it possible to promote the student’s full development, but to have the necessary human and material resources available at an educational level to provide an appropriate response which promotes both their maximum academic and social development. Given the existence of an associated neurological and socioemotional basis, this may have an impact on the self-esteem and motivation of these students as well as on their self-perception, academic performance and social integration [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%